Contribution of micro‐motion to backside wear in a fixed bearing total knee arthroplasty. Issue 11 (16th March 2016) - Levine, Rayna A.C.; Lewicki, Kathleen A.; Currier, John H.; Mayor, Michael B.; Van Citters, Douglas W.
ABSTRACT: This study seeks to identify important factors related to backside wear of tibial inserts in vivo and determine an appropriate wear model for backside wear. An IRB approved database was queried for tibial inserts of a single design from one manufacturer that exhibited evidence of rotatory motion on the backside of the polyethylene. These devices were measured for volumetric wear using a previously established protocol. Features including the change in locking lip width and measurement of micro‐motion marks were used to describe the motion pattern. Volumetric wear and implant characteristics were compared using linear regressions by modeling wear theories suggested by Archard and Wang to determine the most appropriate model for backside wear. The Wang model showed that duration, adjusted sliding distance, and cross‐shear index accounted for approximately 58% of the volumetric wear variation while adjusted sliding distance and duration in vivo accounted for approximately 35% of the volumetric wear variation in the Archard model. Patient weight ( p  = 0.750), patient BMI ( p  = 0.680), and backside area ( p  = 0.784) of the tibial insert were all found to be non‐significant in the Wang model. Similarly, patient weight ( p  = 0.233), patient BMI ( p  = 0.162), and backside area ( p  = 0.796) were found to be non‐significant in the Archard model. Multidirectional micro‐motion appears to contribute significantly to the wear of these components, supporting the Wang theory of cross‐shear for polyethylene wear. Cross‐shear of polymers on an unpolished titanium tray can lead to an increase in wear debris in the body. Care should be taken when designing locking mechanisms and tray designs. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1933–1940, 2016.